2015
DOI: 10.1111/clr.12730
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of wide dental implant: systematic review and meta‐analysis

Abstract: Placement of wide-diameter implants demonstrated a promising survival rate during 5-year follow-up. Further controlled trials with the control group and longer follow-up period are needed to provide the direct evidence comparing survival rates of wide implants with survival rates of narrower implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 53 publications
1
18
0
3
Order By: Relevance
“…19,22 Greater diameter implants have a larger bone-to-implant contact area, higher resistance to fracture and higher initial stability, and create less stress in bone. 8,23 However, in the clinical setting, the use of wide implants is limited by the thickness of the residual alveolar ridge. Yu et al suggested that the implant diameter should be at least half the ridge width; however, narrower alveolar ridges can increase bone stress in narrow bone walls along the implant and may result in rapid bone resorption, which decreases the crown-root ratio and further aggravates the stress accumulation in the crestal bone.…”
Section: Discussionmentioning
confidence: 99%
“…19,22 Greater diameter implants have a larger bone-to-implant contact area, higher resistance to fracture and higher initial stability, and create less stress in bone. 8,23 However, in the clinical setting, the use of wide implants is limited by the thickness of the residual alveolar ridge. Yu et al suggested that the implant diameter should be at least half the ridge width; however, narrower alveolar ridges can increase bone stress in narrow bone walls along the implant and may result in rapid bone resorption, which decreases the crown-root ratio and further aggravates the stress accumulation in the crestal bone.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 However, the findings of the present systematic review should be analysed with caution due to the small number of randomized clinical trials included, which can be considered a limitation. In addition, other factors such as number/position, 14 connection type, 42 length/diameter of the implant, 43,44 loading protocol 45 and follow-up period 1 are considered as influencing factors; unfortunately, sub-analyses could not be performed to verify the influence of these variables in association with the attachment system. Further randomized clinical trials are needed to evaluate these factors in patients with a longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…8 Early studies reported failure rates as high as 20%, probably due to poorly understood indications, different surgical protocols, poor bone quality and the associated learning curve. [17][18][19] More recent prospective studies, however, reported a 97% cumulative survival rate after 5 years 20 and an overall mean cumulative bone loss of 0.57 mm after at least 1 year. 21 For immediate molar replacement, a wide diameter implant yields multiple advantages.…”
Section: Introductionmentioning
confidence: 99%